Building Primary Preservice Teachers’ Identity as Engineering Educators - Nicholas Lux; Rebekah Hammack; Blake Wiehe; Paul Gannon (Education Sciences, 2022)
The purpose of this qualitative case study was to investigate how two primary preservice teachers built their engineering education identities during a clinical field experience that emphasized engineering education. More specifically, we explored the development of their engineering education identities while facing unforeseen circumstances and unfamiliar engineering content. We used a nested qualitative case study approach that was bounded by a university practicum field experience that took place at the height of the COVID-19 pandemic. Data sources included preservice teacher interviews and reflective field notes. We found that the preservice teachers faced a series of contextual factors in the clinical experience that both afforded and constrained professional learning opportunities that influenced their identity development. The affordances made professional learning opportunities possible, while the constraints limited professional growth. We also found that it was the negotiation of the factors, where the preservice teachers worked to mitigate the effect of the constraints while maximizing the advantages of the affordances, that had the greatest influence on their engineering pedagogical knowledge and engineering teaching self-efficacy. Findings from this study could provide teacher educators with insight into preparing primary teachers for unexpected challenges when teaching engineering, as well as how to best prepare engineering-efficacious teachers.